Distributed objects : meaning and mattering after Alfred Gell - Chua, Liana; Elliott, Mark (Berghahn, 2013)
One of the most influential anthropological works of the last two decades, Alfred Gell's Art and Agency is a provocative and ambitious work that both challenged and reshaped anthropological understandings of art, agency, creativity and the social. It has become a touchstone in contemporary artifact-based scholarship. This volume brings together leading anthropologists, archaeologists, art historians and other scholars into an interdisciplinary dialogue with Art and Agency, generating a timely re-engagement with the themes, issues and arguments at the heart of Gell's work,